Instructions given with letters of marque against France - Holland, Henry Fox, Baron, 1705-1774 ([ s.n.], 1756)
June 6, 1756 set of instructions given with the letters of marque (a license to fit out an armed vessel and to commit acts that would otherwise have constituted piracy) against France.